Otolaryngologists and their role in vaccination for prevention of HPV associated head & neck cancer - Matthew Shew; Marcia L. Shew; Andrés M. Bur (Taylor & Francis Group, 2019)
As Otolaryngologists we have witnessed a rise in a new disease with human papilloma virus (HPV) associated oropharyngeal squamous cell carcinoma (OPSCC). As of 2018, HPV associated OPSCC has surpassed the incidence of HPV associated cervical cancer within the United States. Non-HPV related head and neck cancer is largely a preventable disease through avoidance of various environmental factors, and we have seen a significant decline in cancer rates through anti-tobacco campaigns and other public health efforts. Given the success of HPV vaccination campaigns and reduction in HPV associated cervical and other anogenital cancers, some would argue HPV OPSCC is largely a preventable disease through vaccination as well. The question remains is how do we as otolaryngologist, non-primary care providers yet surgeons for this disease, help to promote public health efforts to reduce HPV related OPSCC. Within this article, we discuss preliminary data that supports HPV vaccination with HPV related OPSCC and the ongoing needs by our profession to help support public efforts in reducing the burden of this HPV related cancer.